A huge retroperitoneal cyst with a rare clinical presentation. Issue 12 (20th December 2022) - Alqaisi, Hayder; Wanders, Alkwin; Naujokaite, Gintare; Pedersen, Lasse
Abstract: A 39-year-old male presented with deep venous thrombosis in the right lower limb. He had been experiencing increasing abdominal girth over several years, but this went undetected at the initial examination. Eighteen months later, a computed tomography was conducted, showing a huge retroperitoneal cyst (25 × 23 × 16 cm) lifting the right external iliac vessels. Complete surgical excision of the cyst was performed. The cyst was unilocular and contained 5 l of clear fluid. Histopathology examination found a thin cyst wall consisting of fibrous stromal tissue with a single-layer epithelium lining. Immunohistochemical staining revealed positivity for endothelial cell markers, CD31 and CD34, but negativity for the lymphatic marker podoplanin (D2–40), corresponding to a vascular origin, likely a venous malformation.